Genetic Contribution to Degeneration and Repair Potentials of the Intervertebral Disc in Mice. Issue 1 (April 2016) - Xiong, Chi; Li, Yan; Rai, Farroq Muhammad; Sandell, Linda; Zhang, Ying; Song, You Qiang; Cheah, Kathryn S. E.; Sham, Pak; Chan, Danny
Introduction: Intervertebral discs degenerate with age affected by environmental and genetic factors. Presently, there are no direct biological cures as the etiology of disc degeneration is still not well understood. Enchantingly, nearly 10% population are "protected" from intervertebral disc degeneration even above the age of 50. It is most possibly ascribed to genetic causes manipulating disc homeostasis, maintenance or repair mechanism. The LG/J mice possess outstanding healing capability for damages to elastic and articular cartilages, in contrast to the poor healer SM/J mice. Using these parental strains of mice and the recombinant inbreeds, we assessed the potential genetic contributions to degenerative and protective effects on the intervertebral disc. Material and Method: The parental LG/J and SM/J mice together with recombinant inbreeds (RI) LGXSM-6 (80% of LG/J, 20% of SM/J) and LGXSM-33 (50% of LG/J, 50% of SM/J) were studied. Tail discs at P10, 4 weeks and 8weeks of age were assessed with a quantitative histological degeneration scoring system that has been established. The genetic regions common to parental and RIs were assessed with SNP markers for potential degenerative and protective genes, and functional relationship to disc biology assessed using gene ontology and gene network association with the variants from the RI mouse panel. Results: In the absence of any environmental perturbation, SM/J mice display early signs of disc degeneration. In contrast, the IVD in LG/J mice remained "healthy" at the same age with vacuolated NP cells, while the nucleus pulposus (NP) in SM/J are degenerative in nature with an undefined NP structure that appear fibrotic. Both LGXSM-6 and LGXSM-33 have even higher degenerative scores than SM/J, suggesting that part of the "protective" loci from LG/J may be absence in these RIs. A more detailed analysis of the overlapping genetic region (less than 20% of the whole genome) contains 178 SNP makers (Herbek et al., 2006) on 87 nearby genes. Unsupervised Gene Ontology analyses identified multiple biology processes enriched in transportation of ions and lipid, channel activity and membrane, cytoskeleton organization, immune response, cell adhesion, migration, cell cycle progression and posttranslational protein modifications for the set of genes. Genes that correlated to immune system and skeletal development included VDR, Ano6, Mttp, Bmpr, and Cep112 informed to be share high associated or have frequent variation. Conclusion: LG/J mice have enhanced disc homeostasis and superior healing potential, with a protective effect against disc degeneration. Preliminarily analysis of the gene set (87 genes) suggests changes in the transportation of ions and lipid, and membrane and channel activity may involve in disc function and maintenance. The genomic data can also be used for advanced mapping of the susceptible healing genes identified in articular cartilage repair. It is also promising to map this set of genes across the human whole exome sequencing data that we have generated from 750 individuals for disc degeneration in our population cohort, including elderly with a normal (protect) disc to assess their relevance in our human population study. Acknowledgment: This worked is supported by funding from AOSPINE(SRN2012_8), and China's National strategic basic research program("973") Grant2014CB942901.